2019
DOI: 10.1001/jamanetworkopen.2019.17862
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Greenness Surrounding Schools and Kindergartens and Attention-Deficit/Hyperactivity Disorder in Children in China

Abstract: IMPORTANCE Few studies have investigated the association between greenness and childhood attention-deficit/hyperactivity disorder (ADHD). OBJECTIVE To evaluate the association between greenness surrounding schools or kindergartens and symptoms of ADHD in children. DESIGN, SETTING, AND PARTICIPANTS This population-based cross-sectional study was performed between April 2012 and January 2013 in 7 cities in northeastern China. This analysis included 59 754 children (aged 2-17 years) from 94 schools and kindergart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
49
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(55 citation statements)
references
References 46 publications
5
49
0
1
Order By: Relevance
“…These findings indicate that living in a residential area with higher density of green space in early life may lower the risk of developing ADHD. Our results are supported by previous studies, which also found associations between higher levels of residential green space and lower risk of ADHD (Amoly et al 2014;Donovan et al 2019;Markevych et al 2018;Yang et al 2019) and lower severity of ADHD symptoms (Amoly et al 2014).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…These findings indicate that living in a residential area with higher density of green space in early life may lower the risk of developing ADHD. Our results are supported by previous studies, which also found associations between higher levels of residential green space and lower risk of ADHD (Amoly et al 2014;Donovan et al 2019;Markevych et al 2018;Yang et al 2019) and lower severity of ADHD symptoms (Amoly et al 2014).…”
Section: Discussionsupporting
confidence: 92%
“…2019 ; Markevych et al. 2018 ; Yang et al. 2019 ) and lower severity of ADHD symptoms ( Amoly et al.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although ADHD symptoms were only ascertained from parents, the pattern of phenotypic findings is consistent with other epidemiological results in ADHD, supporting the overall validity of their phenotypic strategy. 1 As Yang et al 1 which features exert which effects at what periods of the life span. 5 Individuals' experience of nature should also be considered, including the types of interaction (eg, swimming in the ocean vs walking in a city park), dose-response of nature exposure, and how personal characteristics affect response.…”
mentioning
confidence: 99%